Groundwater Inflows to the Columbia River Along the Hanford Reach and Associated Nitrate Concentrations - Conner, Abigail; Gooseff, Michael N.; Chen, Xingyuan; Arntzen, Evan; Garayburu-Caruso, Vanessa (Frontiers in Water, 2021)
Healthy river ecosystems require the interaction of many physical and biological processes to maintain their status. One physical process supporting biogeochemical cycling is hydrologic exchange (i.e., hydrologic exchange flows, HEFs) between relatively fast-flowing channel waters and slower-flowing surface and subsurface waters (lateral and vertical). Land uses adjacent to rivers have the potential to alter the water quality of off-channel surface and subsurface waters, and HEFs therefore have the potential to deliver these solutes to rivers. HEFs are nonpoint sources of pollution, making the ultimate pollution source difficult to identify, especially in large rivers. Here we seek to identify HEFs in the Columbia River near Richland, WA by looking for anomalies in temperature and electrical conductivity (EC) along the bed of the river in February, June, July, August, and November 2018. These are ultimately the ‘ends’ of HEFs as they are locations of subsurface inflow to the river. We found these anomalies to be a combination of warmer or colder and higher (but not lower) EC than river water. We identified a majority of warm anomalies in February and July 2018, and majority cold anomalies in June, August, and November 2018. High-EC anomalies were found mostly in February, August, and November. Combined, we observe a shift from warm, high EC anomalies dominating in February to equivalent EC, warm anomalies in June, to equivalent EC, cool anomalies dominating July. In July and August, we measured dissolved nitrate (NO3-) in-situ to determine whether anomalies were associated with increased NO3- loading to the river, especially along the eastern shoreline, which is dominated by agricultural land use. Inflows along the eastern shoreline have greater concentrations of nitrate than river water (up to 40 mg N-NO3-/L), levels that may be toxic to newly-hatched salmon. If these high-NO3- inflows from irrigation-influenced groundwater are at their peak during salmon spawning season, when salmon lay eggs in shallow water, this could negatively impact salmon spawning success.